Optimal Follow-Up Duration for Assessment of Birth Defects After In Vitro Fertilization–Embryo Transfer: A Multicenter 5-Year Cohort Study in China - Liu, Chun-Lin; Li, Ping; Cai, Gui-Feng; Morse, Abraham; Liu, Jun; Chen, Zhi-Heng; Zhang, Xiu; Sun, Ling (Frontiers in Endocrinology, 2022)
Objective: To investigate the impact of 5-year follow-up on the incidence of identified birth defects in children conceived using assisted reproductive technologies (ART). Methods: A five-year cohort study was performed in three ART centers from January 2013 to October 2018. 1,543 women with 1,985 infants who delivered successfully or underwent termination of pregnancy due to malformations were recruited in this study. Follow-up was conducted by phone interview, 7days, 1 year, 3 years and 5 years after birth. Collected data included whether one or more birth defect was diagnosed, the category of birth defects and when the malformation was diagnosed. Cumulative incidence of birth defects and the lost to follow-up rate of each follow-up was compared. Results: According to the diagnostic criterion of birth defects, 111 cases of one or more birth defects were recorded, with a total of 117 birth defects after 5-years’ follow-up. 0.2% (4/1,985) of birth defects were diagnosed before delivery; 2.7% (54/1,985) at 7-days; 5.0% (100/1,985) after one year; 5.5% (109/1,985) after 3 years and 5.6% after (111/1,985)5 years. 3.4% (4/117) of defects were diagnosed prenatally, 45.3% (53/117) of defects diagnosed within the first 7 days after delivery, 40.2% (47/117) diagnosed during 7 days to 1 year, and 9.4% (11/117) of defects diagnosed in 1-3 years after birth. The remaining 1.7% (2/117) of defects were diagnosed between the ages of 3 and 5 years. Among the 1,543 patients, 99.9% patients (1,542/1,543) responded telephone interview at 7-days after delivery, the response rate was 89.0% (1,373/1,543) at 1-year, 81% (1,250/1,543) at 3 years, and 64.5% (995/1,543) after 5 years. Conclusion: We suggest that in ART, 1-year follow-up should be the minimum requirement and 3 years follow up the optimal length of follow-up that balances resource requirements with ascertainment completeness.